Por uma pedagogia surda : narrativas de licenciandos surdos da área das ciências naturais-química - Amoedo, Francisca Keila de Freitas (2023)
In Brazil, the presence of deaf people in educational institutions is a major challenge of official policies. Although there have been advances in recent decades in terms of inclusion, we must consider that it is not enough to guarantee them the right of access to formal education. It is also imperative to guarantee their permanence in schools and universities, which implies considering the assumptions of Deaf Pedagogy. This issue is adopted as the object of study of this research, which is guided by the objective: To analyze narratives of deaf scholars about their experiences in the undergraduate course in Chemistry at CESP-UEA, in order to view pedagogical aspects demanded by the deaf person. This is a participant research that involved deaf researchers at the Amazonas State University - Parintins Campus. This methodological option is justified by the understanding that it is not appropriate to treat deaf students as mere informants of data, since they have life experiences that can enhance the production of research carried out in collaboration, especially when it comes to education that interests the deaf people. The experiences narrated within this study made the deaf scholars to exercise protagonism as teachers in training in a context in which the changes resulting from the pandemic caused by the covid-19 required new methods of teaching and learning. These experiences were narrated by the participants individually through video, then were transcribed by the Transcriber program, organized and returned to the research participants who could expose their considerations, remove or add what they considered relevant. Afterwards, the narratives were submitted to the Iramuteq software. The theoretical support for the development of the analysis is based on cultural studies, more specifically, in the field of deaf studies. Priority is given to deaf authors who express theoretical positions in favor of Deaf Pedagogy. Data indicate that in CESP-UEA has been occurring advances in the field of inclusion policies for the deaf, especially in undergraduate courses. The narratives of deaf undergraduate students in chemistry indicate that deaf people have interests in this area of knowledge and, based on experiences in the course, can contribute to the production of inclusion policies in basic education, particularly with regard to education in natural sciences and chemistry.